What Works and for Whom? Effectiveness and Efficiency of School Capital Investments Across the U.S. - Barbara Biasi; Julien Lafortune; David Schönholzer (The Quarterly Journal of Economics, 2025)
ABSTRACT This article identifies which investments in school facilities help students and which are valued by homeowners. Using novel data on school district bonds, test scores, and house prices across 29 U.S. states and a research design based on narrowly decided elections with staggered timing, we find that increased capital spending in schools significantly improves test scores and is efficient on average. However, the effects vary widely depending on the type of project and the characteristics of the school district. Investments in essential infrastructure, such as HVAC systems or pollutant removal, yield notable improvements in student performance, while expenditures on athletic facilities show no measurable academic benefit. Socioeconomically disadvantaged districts gain disproportionately from capital investments, even after accounting for project type, yet these districts typically underinvest in such projects.